2016
DOI: 10.1155/2016/4179862
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Procedure in Case of Urethrocavernous Fistula after Revision Surgery for Malfunctioning Three-Piece Penile Prosthesis

Abstract: Urethrocavernous fistula is a rare complication of penile prosthesis. Literature lacks any materials regarding this complication's treatment. We report our experience with a 66-year-old man who developed urethrocavernous fistula after penile prosthesis implant. Our technique involves the careful closure of urethral and corpus cavernosum defects with application of TachoSil® above the sutures. After the salvage procedure, no recurrence of fistula occurred and patient was able to have sexual intercourse. We beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…Given the risk of fistula formation in catheter-dependent patients, some have reported performing perineal urethrostomy or suprapubic cystotomy at the time of penile prosthesis surgery [11]. Caraceni et al reported a case of urethrocavernous fistula with successful IPP replacement, primary repair of urethral and cavernosal defects augmented by the use of a dry layer of the human coagulation factors fibrinogen and thrombin [12]. Given the paucity of cases of urethral erosion and urethrocavernous fistula secondary to penile prosthesis, no standard of care has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Given the risk of fistula formation in catheter-dependent patients, some have reported performing perineal urethrostomy or suprapubic cystotomy at the time of penile prosthesis surgery [11]. Caraceni et al reported a case of urethrocavernous fistula with successful IPP replacement, primary repair of urethral and cavernosal defects augmented by the use of a dry layer of the human coagulation factors fibrinogen and thrombin [12]. Given the paucity of cases of urethral erosion and urethrocavernous fistula secondary to penile prosthesis, no standard of care has been established.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, blunt trauma, iatrogenic, and idiopathic causes have also been reported. [4][5][6][7][8][9] Patients usually had a delayed presentation of 2 to 5 weeks from the initial inciting event. 2,3,5,6,[8][9][10] Presenting symptoms included dysuria, purulent or foul-smelling urethral discharge, abscess on the penile shaft, or intermittent or pulsatile gross hematuria with erections.…”
Section: Discussionmentioning
confidence: 99%
“…Primary repair or repair with a fibrin seal patch (TachoSil®) or an allograft such as Tutoplast® pericardium has been reported previously with complete resolution. [5][6][7]10 Tachosil® was first described in the setting of pancreatic resections to prevent post-operative pancreatic fistulas. The efficacy of this material in this type of repair has been reported with variable success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of the T-shunt and Al-Ghorab shunts can be improved to nearly 100% when combined with the use of dilators to physically remove stagnant blood within the corpora [ 16 17 18 ]. However, use of dilators is accompanied by an increased risk of urethral injury and possible formation of urethrocavernosal fistulas [ 19 ]. Should distal shunts fail, the use of proximal shunts is warranted.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%